Genetic diversity analysis of Myristica and related genera using RAPD and ISSR markers - R S Shalini, B Krishnamoorthy, T E Sheeja, C Sabeesh, O V Shabna (Journal of Spices and Aromatic Crops, 2013)
Genetic diversity among seven species of Myristica, two of its related genera and an unidentified species was analyzed using 46 PCR markers (30 RAPD and 16 ISSR). This is the first study on molecular genetic diversity of the rare, endangered and endemic Myristica species and its related genera. RAPD and ISSR analyses yielded 497 and 262 bands with 98.1% and 97.3% polymorphism, respectively. By combining markers, a total of 759 bands were detected of which 743 (97.8%) were polymorphic with an average of 16.1 bands per primer. High level of existing genetic variability was evident from the high percentage of polymorphism. Combined analysis of RAPD and ISSR markers resulted in better distinction of species. The mean polymorphic information content (PIC) indicated that both the marker systems are effective in detecting polymorphism either individually or in combination. Similarity coefficient (Jaccards) varied from 0.22 to 0.62 when markers were combined and the pattern was similar to RAPD with a high Mantel matrix correlation (r=0.95). Principal Coordinates Analysis (PCA) conformed to cluster analyses. First three most informative PC components explained 51.1%, 49.3% and 46.5% of total variation. A maximum similarity of (63%) was observed between Gymnocranthera canarica and the unidentified species of Myristica. Knema andamanica and Myristica prainii were found to be the most distinct (17.7%). Similarities at molecular level were close to either the morphological traits (mace and fruit/seed characters) or the geographical location. Species specific bands could be identified from all the accessions under study, which has the potential for development into SCAR (Sequence Characterised Amplified Region) markers for genotype fingerprinting or development of specific DNA probes for identification and authentication.